PERSEPSI MASYARAKAT TERHADAP BSI (BANK SYARIAH INDONESIA) CABANG INDRALAYA (STUDI PADA MASYARAKAT DESA INDRALAYA KECAMATAN INDRALAYA KABUPATEN OGAN ILIR) - Silawati; Hidayani; Darsi Ahmadan (LA RIBA: Jurnal Perbankan Syariah, 2024)
This thesis aims to discuss some of the public's responses or views regarding BSI Syariah Indralaya Branch. In collecting data in the community, researchers chose Indralaya Mulya Village, Indralaya District, Ogan Ilir Regency as the place for research. The results of this research conclude that the presence of Bank Syariah Indonesia (BSI Syariah Indralaya branch) has an important meaning in developing society from an economic aspect to implement Islamic law. The public in various perceptions stated that Sharia Banks must maximize the socialization process in overcoming the lack of public understanding of Sharia Banks. Apart from that, we can also find out the causes of the public's tendency towards conventional banks and the underlying reasons why people do not choose Sharia Banks. Therefore, the presence of BSI Syariah Indralaya Branch is believed to have increased the tight competition in the world of banking, accompanied by the hope of creating new breakthroughs in in order to improve the standard of living of the community while also providing choices for the community regarding views and beliefs regarding bank interest which according to some Ulama is included in the practice of usury which is not in accordance with Islamic Sharia. The method used is a qualitative research method which seeks to describe the phenomena that occur when conducting research on public perceptions of BSI Syariah Indralaya branch. For this reason the author carries out data collection through observation, interviews, documentation, or direct data collection by hand to collect it. data or documents that can provide an overview of locations and objects.